Pendeteksian Potensi Financial Statement Fraud dengan Analisis Fraud Pentagon - Lestari, Widya; Sukartini, Sukartini; Fauzi, Nurul (Prodi Manajemen Universitas Pamulang, 2024)
The aim of this research is to identify potential instances of financial statement fraud using the Fraud Pentagon theory, which includes the elements of pressure, opportunity, rationalization, competence, and arrogance. Pressure is represented by variables such as financial stability, financial targets, and external pressures. Opportunity is measured through the proxy of ineffective monitoring. Rationalization is proxied by changes in auditors. Competence is reflected in director changes. Arrogance is assessed through the frequency and size of CEO pictures. The research population consists of transportation companies listed on the Indonesian Stock Exchange (IDX) between 2020 and 2022. A purposive sampling method was employed, resulting in a sample of 30 companies. The statistical analysis used for this study involves multiple linear regression analysis using SmartPLS software. The research findings indicate that ineffective monitoring has a significant impact on financial statement fraud, whereas the other independent variables do not influence financial statement fraud.